TrOCR: Transformer-based Optical Character Recognition with Pre-trained Models - Li, Minghao; Lv, Tengchao; Chen, Jingye; Cui, Lei; Lu, Yijuan; Florencio, Dinei; Zhang, Cha; Li, Zhoujun; Wei, Furu (AAAI 2023, 2023)
Text recognition is a long-standing research problem for document digitalization. Existing approaches for text recognition are usually built based on CNN for image understanding and RNN for char-level text generation. In addition, another language model is usually needed to improve the overall accuracy as a post-processing step. In this paper, we propose an end-to-end text recognition approach with pre-trained image Transformer and text Transformer models, namely TrOCR, which leverages the Transformer architecture for both image understanding and wordpiece-level text generation. The TrOCR model is simple but effective, and can be pre-trained with large-scale synthetic data and fine-tuned with human-labeled datasets. Experiments show that the TrOCR model outperforms the current state-of-the-art models on both printed and handwritten text recognition tasks. The code and models will be publicly available at https://aka.ms/TrOCR